Pelaksanaan Pendidikan Agama Buddha Pada Sekolah Dasar - Kumari, Winja; Lisniasari, Lisniasari (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The research was conducted with a descriptive qualitative approach. The purpose of this study was to determine the implementation of Buddhist education in elementary schools. In this study, a method known as descriptive qualitative method was used. The research method is descriptive qualitative by describing an event, current event. In other words, this method takes a problem from an actual problem. The learning process of Buddhist teaching subjects, for Buddhist students, at the elementary school level, can be described by applying teaching materials/materials, applying tactics/systems, applying media and applying assessments. The conclusions of this study are the implementation of Buddhist education at the elementary school level still reaping many problems ranging from the competence of Buddhist education teachers who are still lacking, the media used is still limited, training programs are still lacking, and various facilities and infrastructure are not adequate. So that various evaluations are needed so that the implementation of Buddhist education at the elementary school level can run well